The Development of Student Work Sheets Based on Teaching and Learning Approaches to Improve the Capability of Problem Solving of Basic Class IV Students - Eka rahmawati; Irdamurni Irdamurni (Postgraduate School, Universitas Negeri Padang, 2019)
This study discusses the development of an approach-based student worksheet (LKS) (CTL) that is valid, practical, and effective on the topic of statistics in grade IV of elementary school. The research method used is a type of 4D research design by Thiagarajan, Semmel, and Semmel (1974). This research was conducted in four phases, namely defining, designing worksheets, developing, and disseminating in elementary schools. Data was collected using document analysis, observation, interviews, field notes, tests, and questionnaires. The data collected is analyzed qualitatively and quantitatively. Based on the research that has been done, LKS has fulfilled the valid criteria in terms of content, approach, format, and language. The level of validity of the developed LKS is in a very valid category. The results of observations, questionnaires, and interviews showed that LKS was practical in terms of ease of use, use of time, and readability by teachers and students. In addition, LKS developed effectively improves students' problem solving abilities. Students can find statistical concepts with various activities on LKS, namely finding data, analyzing data, collaborating, trying, and solving problems related to everyday life. Keywords: LKS, CTL, Problem solving Skill.